2015
DOI: 10.4048/jbc.2015.18.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Lymph Node-to-Primary Tumor Standard Uptake Value Ratio on Preoperative18F-FDG PET/CT: A Prognostic Factor for Invasive Ductal Breast Cancer

Abstract: PurposeThis study assessed the axillary lymph node (ALN)-to-primary tumor maximum standard uptake value (SUVmax) ratio (ALN/T SUV ratio) in invasive ductal breast cancer (IDC) on preoperative 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) to determine the effectiveness in predicting recurrence-free survival (RFS).MethodsOne hundred nineteen IDC patients (mean age, 50.5±10.5 years) with pathologically proven ALN involvement without distant metastasis and preoperative FDG PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…The strength of the current study is that the SUV LN /SUV Tumor is simple to calculate and may have less inter-scanner variability compared to the SUV LN , and thus SUV LN /SUV Tumor may have better generalizability. In addition, SUV LN /SUV Tumor may reflect the aggressiveness of the primary tumor and the biological interactions between primary tumor and metastatic LNs as indicated by previous studies in other disease sites [22][23][24]26].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The strength of the current study is that the SUV LN /SUV Tumor is simple to calculate and may have less inter-scanner variability compared to the SUV LN , and thus SUV LN /SUV Tumor may have better generalizability. In addition, SUV LN /SUV Tumor may reflect the aggressiveness of the primary tumor and the biological interactions between primary tumor and metastatic LNs as indicated by previous studies in other disease sites [22][23][24]26].…”
Section: Discussionmentioning
confidence: 91%
“…It has been demonstrated that higher SUV LN /SUV Tumor portended lower response to initial chemotherapy and poorer survival (PFS and OS) for patients with nonsmall cell lung cancer [22]. Similarly, it has been observed that SUV LN /SUV Tumor was an independent covariate for predicting relapse in cervical squamous cell carcinoma [26], invasive ductal breast cancer [24], and resectable pancreatic cancer [23].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…node-to-tumor SUV ratio (NTR), is a promising functional biomarker which could be easily acquired without much change of the established work-flow and easily accessible for a retrospective study. NTR has been evaluated for prediction of axillary macrometastasis and prognosis in breast cancer (11,12), nodal staging in non-small-cell lung cancer (13), and prognosis prediction in cervical and endometrial cancer (14,15). We presumed that NTR may also provide prognostic information in patients with unresectable esophageal SCC.…”
Section: -Deoxy-2-[18f]fluoro-d-glucose Positron Emission Tomographymentioning
confidence: 99%